An Update in Imaging of Blunt Vascular Neck Injury. Issue 3 (August 2020) - Abu Mughli, Rawan; Wu, Tong; Li, Jessica; Moghimi, Saba; Alem, Zersenay; Nasir, Muhammad Umer; Abdellatif, Waleed; Nicolaou, Savvas
Traumatic injuries of the cervical carotid and vertebral arteries, collectively referred to as blunt cerebrovascular injury (BCVI), can result in significant patient morbidity and mortality, with one of the most feared outcomes being cerebrovascular ischemia. Systematic imaging-guided screening for BCVI aims for early detection to guide timely management. In particular, accurate detection of the severity and grade of BCVI is paramount in guiding initial management. Furthermore, follow-up imaging is required to decide the duration of antithrombotic therapy. In this article, classification of the grades of BCVI and associated imaging findings will be outlined and diagnostic pitfalls and mimickers that can confound diagnosis will be described. In addition, updates to existing screening guidelines and recent efforts of criteria modification to improve detection of BCVI cases will be reviewed. The advent of postprocessing tools applied to conventional computed tomography (CT) angiograms and new diagnostic tools in dual energy CT for improved detection will also be discussed.